Optimization of clofibrate with O-desmethyl anetholtrithione lead to a novel hypolipidemia compound with hepatoprotective effect. (15th September 2022) - Liu, Haitao; Zhang, Panpan; Ge, Xiaoxiao; Wu, Qiong; Han, Chuchu; Zhang, Linyang; Hua, Yuxin; Zhang, Yuxuan; Liu, Jiping; Shi, Yongheng; Wang, Bin; Wang, Xiaoping; et al.
Graphical abstract: Highlights: CF-ATT was designed and synthesized, which showed a significant activity of reducing TG and TC. CF-ATT displayed potent antioxidant, anti-inflammatory and hepatoprotective effects. The hepatoprotective mechanism was through the Nrf2/NF-κB signaling pathway. Abstract: Oxidative stress and inflammation were considered to be the major mechanisms in liver damage caused by clofibrate (CF). In order to obtain lipid-lowering drugs with less liver damage, the structure of clofibrate was optimized by O-desmethyl anetholtrithione and got the target compound clofibrate-O-desmethyl anetholtrithione (CF-ATT). CF-ATT significantly reduced the levels of plasma triglycerides (TG), total cholesterol (TC) in hyperlipidemia mice induced by Triton WR-1339. In addition, CF-ATT has a significantly protective effect on the liver compared with CF. The liver weight and liver coefficient were reduced. The hepatic function indexes were also decreased, such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP). Histopathological examination of the liver revealed that inflammatory cell infiltration, nuclear degeneration, cytoplasmic loosening and hepatocyte necrosis were ameliorated by administration with CF-ATT. The hepatoprotective mechanism showed that CF-ATT significantly up-regulated Nrf2 and HO-1 protein expression and down-regulated p-NF-κB P65 expression in the liver. CF-ATT has obviously antioxidant and anti-inflammatory activity. These findings suggested that CF-ATT has significant hypolipidemia activity and exact hepatoprotective effect possibly through the Nrf2/NF-κB-mediated signal pathway.